Meningkatkan Kerjasama Dan Hasil Belajar Siswa Kelas Vii.A Pada Mata Pelajaran Ppkn Melalui Metode Learning Community Di Smp Negeri 1 Pujut - Agustina Dewi, Baiq Almalika (Jurnal Ilmiah Mandala Education (JIME), 2023)
This study aims to improve cooperation and student learning outcomes in class VII.A through the method Learning Community. The benefits of this research are expected to contribute to schools as an alternative to improve teacher quality and performance through study class action so that the quality, process and results of student learning in subjects PPKn in particular, and all subjects in general. The method used is classroom action research (PTK) using two cycles, namely the first cycle and the second cycle, each cycle has four stages, namely the action planning stage (Planning), application of the action (Action), observing and evaluating the process and results of actions (Observation and evaluation), and reflect on what is expected to be achieved (Success criteria). Data collection techniques were carried out by observation, tests, interviews and documentation, participants. The results of this study obtained data on the application of learning methods Learning Community can improve cooperation and student learning outcomes in class VII.A on subjects PPKn SMP Negeri 1 Pujut